Dinamika tradisi Ncangi Punowu di Dusun Sungai Bangun Kecamatan Bonti Kabupaten Sanggau Dalam Kurun Waktu 2010-2020 - Hajijah, Siti (Peneliti.net, 2025)
This research is to find out the dynamics of the Ncangi Punowu tradition in the 2010-2020 period, and the role of the community in preserve it, in Sungai Bangun hamlet, Bonti District, Sanggau Regency. This research used historical research methods consisting of; Topic Selection, Heruistics, Verification, Interpretation, Historiography. Interpretation, Historiography. The results of this research indicated that; Ncangi Punowu implementation equipment, namely; one plate and two bowls of rice, one bowl of pulut rice, one redeemed egg, one bottle of Tuak, four sticks of Ajat'n, and four Sungki, two sticks of Titia, one chicken. Its implementation starts from the Ngu’duw to determine the, making Mparo, Mpo’do Onto, Mpo’do Sa’a.; The dynamics of the Ncangi Punowu occur in the habits of the community and Babat’n which is starting to not fit in, in the procession of implementation there is no change.; The role of the community in preserve it is by continuing to carry it out every year. Preparation for the implementation is carried out from the Ngu’duw, making Mparo. The implementation consists of Mpo’do Onto and Mpo’do Sa’a. There were no changes in the process of implementing. The preservation of Ncangi Punowu is by carrying it out every year.